Hematological and Serum Chemistry of Canine Parvoviral Enteritis in Diverse Breeds of Dogs - Olaifa, Olanrewaju Samuel; Kolawole , Aderonke Rachel; Akanbi, Olatunde Babatunde; Odita, Christiana Ibironke; Taiwo, Victor (Media Kedokteran Hewan, 2025)
Canine Parvovirus enteritis (CPV-2) is a highly infectious viral disease occurring in puppies resulting in high mortality with a myriad of clinical signs, hematological and biochemical changes during the progression of the disease. This study investigated hematological and biochemical changes in 30 CPV-positive dogs in Ibadan, Nigeria. Severe non-regenerative anemia (35.71%) and leukopenia (22 cases) were prevalent. Thrombocytopenia was severe in 73.33% of cases. Further analysis revealed normocytic hypochromic anemia in 42.86%, microcytic hypochromic anemia in 28.57%, and leukopenia categorized as mild (5), moderate (12), or severe (5). Biochemical changes included hyperproteinemia (26.7%), hyperalbuminemia, hyperglobulinemia, and elevated liver enzymes in some cases. Renal dysfunction was evident in 16.7% of dogs with elevated creatinine. Significant differences (p<0.05) were observed between infected and healthy dogs. These findings underscore the critical impact of CPV on hematological and biochemical profiles, necessitating supportive care and emphasizing the crucial role of vaccination in disease prevention.